The Palliative Care Interdisciplinary Team: Where Is the Community Pharmacist? - O'Connor, Moira; Pugh, J.; Jiwa, Moyez; Hughes, Jeffery; Fisher, C. (Centre for Bioethics, IRCM, 2011)
Palliative care emphasizes an interdisciplinary approach to care to improve quality of life and relieve symptoms. Palliative care is provided in many ways; in hospices, hospital units, and the community. However, the greatest proportion of palliative care is in the community. In hospice and palliative care units in hospitals, clinical pharmacists are part of the interdisciplinary team and work closely with other health care professionals. Their expertise in the therapeutic use of medications is highly regarded, particularly as many palliative care patients have complex medication regimens, involving off-label or off-license prescribing that increases their risk for drug-related problems.However, this active involvement in the palliative care team is not reflected in the community setting, despite the community pharmacist being one of the most accessible professionals in the community, and visiting a community pharmacist is convenient for most people, even those who have limited access to private or public transport. This may be due to a general lack of understanding of skills and knowledge that particular health professionals bring to the interdisciplinary team, a lack of rigorous research supporting the necessity for the community pharmacist's involvement in the team, or it could be due to professional tensions. If these barriers can be overcome, community pharmacists are well positioned to become active members of the community palliative care interdisciplinary team and respond to the palliative care needs of patients with whom they often have a primary relationship.